Application of System-level Analysis Method in Fan-driven Gearbox Test - Lü Zuopeng; Jian Luo; Jin Feng; Lulu Qian; Zhongtao Huang (Jixie chuandong)
The fan-driven gearbox is characterized by complex structure and difficult system dynamics analysis. The accuracy of the component level model is verified through the modal analysis and the percussion modal test of the gearbox component. Then the rationality of the subsystem structure analysis is verified through the comparative analysis of the dynamic response analysis and performance test of the external meshing subsystem. Finally， through the mode synthesis method， each subsystem is unified into the internal meshing system for dynamic response calculation， and it is analyzed and verified with the test data. The key points of analysis and verification of each part are clarified and iterated step by step. A set of system-level analysis methods for theoretical analysis and test verification from component level to subsystem level and then to system level are established， so as to provide guidance and help for the parametric sensitivity analysis and modal identification of complex systems in the future.